Altemeier’s procedure for complete rectal prolapse; outcome and function in 43 consecutive female patients - Mario Trompetto; Roberta Tutino; Alberto Realis Luc; Eugenio Novelli; Gaetano Gallo; Giuseppe Clerico (2019)
The aim of this retrospective study was to evaluate morbidity, mortality, postoperative function and recurrences in patients treated by Altemeier's rectosigmoidectomy for complete rectal prolapse in a referral center for pelvic floor functional disorders. Peri-operative data on 43 consecutive female patients were reviewed. At follow-up any change in pelvic floor function and recurrences were determined. Thirty four patients were assessed at a median interval of 49 (2–135) months, six being deceased for reason not related to the prolapse and three lost to follow-up. Post-operative complications at 30 days occurred in 18 patients (38%). Major complication occurred in only one patient that was pneumonia with lung failure. Major complications were not related to the ASA score, BMI or age [average age 76.4]. There was no post-operative mortality at 30 days. At long-term follow-up functional results demonstrate a statistically significant decrease in the Obstructive Defecation Syndrome (ODS) score, but no statistically significant changes in the Vaizey score, the International Consultation on Incontinence Questionnaire Short Form (ICIQ-SF) score and the urinary retention score. ODS score decreased with respect to levatorplasty and the change was statistically significant instead of Vaizey score in which were not. At the same follow-up there were 12 (35%) cases of recurrence with an estimated risk at 48 months of 40%. There were no statistically significant differences between patients with and without recurrence regarding age (p = 0.188), BMI (p = 0.864), ASA score (p = 0.433), previously repaired prolapse (p = 0.398), previous hysterectomy (p = 0.705), length of resected bowel (p = 0.126), and levatorplasty (p = 0.304). Patient satisfaction showed a mean of 8.8 and 6.4 respectively in patients without and with recurrences (p = 0.012). Altemeier's procedure had in our series low complications rate and no mortality. It offered improved evacuation in constipated patients while didn't improve fecal and urinary continence. Recurrence of prolapse was 40% at four years.